Inhibition of PIM Kinases in DLBCL Targets MYC Transcriptional Program and Augments the Efficacy of Anti-CD20 Antibodies - Szydłowski, Maciej; Garbicz, Filip; Jabłońska, Ewa; Górniak, Patryk; Komar, Dorota; Pyrzyńska, Beata; Bojarczuk, Kamil; Prochorec-Sobieszek, Monika; Szumera-Ciećkiewicz, Anna; Rymkiewicz, Grzegorz; Cybulska, Magdalena; Statkiewicz, Małgorzata; et al. (Cancer research, 2021)
The family of PIM serine/threonine kinases includes three highly conserved oncogenes, PIM1, PIM2, and PIM3, which regulate multiple prosurvival pathways and cooperate with other oncogenes such as MYC. Recent genomic CRISPR-Cas9 screens further highlighted oncogenic functions of PIMs in diffuse large B-cell lymphoma (DLBCL) cells, justifying the development of small-molecule PIM inhibitors and therapeutic targeting of PIM kinases in lymphomas. However, detailed consequences of PIM inhibition in DLBCL remain undefined. Using chemical and genetic PIM blockade, we comprehensively characterized PIM kinase-associated prosurvival functions in DLBCL and the mechanisms of PIM inhibition-induced toxicity. Treatment of DLBCL cells with SEL24/MEN1703, a pan-PIM inhibitor in clinical development, decreased BAD phosphorylation and cap-dependent protein translation, reduced MCL1 expression, and induced apoptosis. PIM kinases were tightly coexpressed with MYC in diagnostic DLBCL biopsies, and PIM inhibition in cell lines and patient-derived primary lymphoma cells decreased MYC levels as well as expression of multiple MYC-dependent genes, including PLK1. Chemical and genetic PIM inhibition upregulated surface CD20 levels in an MYC-dependent fashion. Consistently, MEN1703 and other clinically available pan-PIM inhibitors synergized with the anti-CD20 monoclonal antibody rituximab in vitro, increasing complement-dependent cytotoxicity and antibody-mediated phagocytosis. Combined treatment with PIM inhibitor and rituximab suppressed tumor growth in lymphoma xenografts more efficiently than either drug alone. Taken together, these results show that targeting PIM in DLBCL exhibits pleiotropic effects that combine direct cytotoxicity with potentiated susceptibility to anti-CD20 antibodies, justifying further clinical development of such combinatorial strategies. SIGNIFICANCE: These findings demonstrate that inhibition of PIM induces DLBCL cell death via MYC-dependent and -independent mechanisms and enhances the therapeutic response to anti-CD20 antibodies by increasing CD20 expression.
Keywords: regulace genové exprese u nádorů; Animals; proliferace buněk; apoptóza; Female; protoonkogenní proteiny c-pim-1; inhibitory proteinkinas; myši SCID; Proto-Oncogene Proteins c-pim-1; ženské pohlaví; Apoptosis; Gene Expression Regulation, Neoplastic; lidé; Proto-Oncogene Proteins c-myc; Mice; difúzní velkobuněčný B-lymfom; Rituximab; protoonkogenní proteiny c-myc; nádorové buňky kultivované; Antigens, CD20; Mice, SCID; myši; Lymphoma, Large B-Cell, Diffuse; Phosphorylation; protinádorové látky imunologicky aktivní; xenogenní modely - testy protinádorové aktivity; Tumor Cells, Cultured; fosforylace; Protein Kinase Inhibitors; rituximab; antigeny CD20; Cell Proliferation; Xenograft Model Antitumor Assays; zvířata; Antineoplastic Agents, Immunological; Humans